Post-mortem computed tomography (PMCT) and PMCT-angiography after transvascular cardiac intervention - Vogel, Beatrice; Heinemann, Axel; Gehl, Axel; Hasegawa, Iwao; Höpker, Wilhelm-Wolfgan; Poodendaen, Chanasom; Tzikas, Antonios; Gulbins, Helmut; Reichenspurner, Hermann; Püschel, Klaus; Vogel, Hermann (Archiwum Medycyny Sądowej i Kryminologii/Archives of Forensic Medicine and Criminology, 2013)
Background and Purpose: During the last years, Post Mortem Computed Tomography (PMCT) has become an integral part of the autopsy. PMCT-angiography may augment PMCT. Both exams have proven their value in visualizing complications after heart surgery. Therefore, they should also show complications after transvascular interventions. This assumption initiated our project: to evaluate the possibilities of PMCT and PMCT-angiography after transvascular cardiac interventions. Material and Methods: In our archives of characteristic and typical PMCT findings, we searched for observations on preceding transvascular cardiac interventions. Additionally, we reviewed our PMCTangiographies (N=140). Results: After transvascular cardiac interventions, PMCT and PMCT-angiography visualized bleeding, its amount and its origin, cardiac tamponade, free and covered perforations, transvascular implanted valves and their position, catheters and pacemakers with fractures, abnormal loops and bending. Bubbles in the coronary vessels (indicating air embolism) become visible. Conclusion: After transvascular cardiac interventions, PMCT and PMCT-angiography show complications and causes of death. They prove a correct interventional approach and also guide autopsy. In isolated cases, they may even replace autopsy.